2016
DOI: 10.5812/ircmj.28076
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effects of Diazinon on Fetal Liver in BALB/c Mice

Abstract: BackgroundDiazinon is an organophosphate that is broadly used as a pesticide to control insects and environmental pollutions. This toxic material is absorbed via inhalation, contact, or digestion and affects different tissues.ObjectivesThis research was a histomorphometric and immunohistochemical study of the fetal liver of mice after exposure to Diazinon.Materials and MethodsTwenty-five pregnant BALB/c mice (25 - 30 gr) were divided into five equal groups in the animal lab of Baqiyatallah University of Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…Forty-minute inhalation of diazinon every other day in pregnant mice induced a dosedependent increase in the hepatocyte area, hepatocyte apoptosis, and a decrease in the sinusoid area of the foetal liver (40).…”
mentioning
confidence: 95%
“…Forty-minute inhalation of diazinon every other day in pregnant mice induced a dosedependent increase in the hepatocyte area, hepatocyte apoptosis, and a decrease in the sinusoid area of the foetal liver (40).…”
mentioning
confidence: 95%
“…DZN induced oxidative stress and lipid peroxidation by enhancing the formation and aggregation of reactive oxygen species (ROS), which is initiating brain damage and secondary apoptosis [Sargazi et al, 2015;Saraei et al, 2016;Anbarkeh et al, 2019]. A comparable finding was noticed by Imosemi and Osinubi [2011].…”
Section: Dzn Toxicity Altered the Ache Levelmentioning
confidence: 79%
“…In comparison to the control groups, a significant increase in fetal weight at birth and at PD7 was detected with a significant decrease at PD14. The body weight is an accurate indicator of the developmental toxicity in neonatal pups [Allam et al, 2011] and previous studies observed an increase in fetal weight at birth after prenatal exposure to DZN [Saraei et al, 2016] and a decrease at PD21 in mice prenatally treated by chlorpyrifos [Ambali et al, 2009]. These findings clarified that the OP-induced teratogenic effect had been triggered by passing through the placenta, which is accompanied by poor clearance and detoxification system in the immature fetus [Tayaa et al, 2015;Indu et al, 2016].…”
Section: Dzn Induced Changes In Offspring's Fetal Weightmentioning
confidence: 99%
“…16 Research done by Saraei et al revealed that inhalation of Diazinon by pregnant mice increased the apoptosis in the developing hepatocytes. 17 The liver sections of rats belonging to group III showed normal histological structure of the hepatic tissue. Normal arrangement of hepatocytes was observed.…”
Section: Discussionmentioning
confidence: 90%